Feedback and star formation in AGNs. Issue Volume 15:Issue S356(2019) (October 2019) - Ho, Luis C.
Abstract: I will describe a series of experiments designed to use measurements of the cold ISM content of quasars to constrain the effectiveness of AGN feedback. I will propose new star formation rate indicators and apply them to constrain the star formation rate in quasars.